Greybody factors of black holes in dRGT massive gravity coupled with nonlinear electrodynamics - Kanzi, Sara; Mazharimousavi, S. Habib; Sakalli, Izzet (Academic Press Inc Elsevier Science, 2020)
In the context of the dRGT massive gravity coupled with nonlin-ear electrodynamics, we present new dRGT black hole solutions. Together with the thermodynamical properties of the solutions, we study the greybody factor of the corresponding black hole solution. To this end, we compute the rigorous bound on the greybody factor for the obtained dRGT black holes. The obtained results are graphically represented for different values of the theory's physical parameters. Our analysis shows that the charged dRGT black holes of nonlinear electrodynamics evaporate quicker than the charged dRGT black holes originated from linear electrodynamics. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Hawking radiation; dRGT massive gravity; Greybody factor; Exact solution; Klein-Gordon equation